Strategi Komunikasi Humas Polda Daerah Istimewa Yogyakarta Dalam Membangun Kepercayaan Masyarakat Terhadap Kepolisian Dalam Menangani Kejahatan Jalanan - Nurkholis Adi Pamungkas (Riviera Publishing, 2025)
This study aims to determine the communication strategy carried out by the Yogyakarta Special Region Police Public Relations in building public trust in the police, especially in handling street crimes that are rampant in the Yogyakarta area. Street crimes or what are known to the public as